2009
DOI: 10.1111/j.1939-165x.2009.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of semiquantitative test strips, urine protein electrophoresis, and an immunoturbidimetric assay for measuring microalbuminuria in dogs

Abstract: UPE and semiquantitative test strips are less accurate than the automated immunoturbidimetric method for the measurement of albumin in canine urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…A study comparing semiquantitative test strips and quantitative albumin assessment indicated that 29% of dogs with measurable MA of > 1.4 mg/L were negative using the semiquantitative test strips, whereas 71% were positive. Using 10 mg/L as a cut‐off for MA, the test strips had false‐negative and false‐positive rates of 9 and 8%, respectively …”
Section: Discussionmentioning
confidence: 99%
“…A study comparing semiquantitative test strips and quantitative albumin assessment indicated that 29% of dogs with measurable MA of > 1.4 mg/L were negative using the semiquantitative test strips, whereas 71% were positive. Using 10 mg/L as a cut‐off for MA, the test strips had false‐negative and false‐positive rates of 9 and 8%, respectively …”
Section: Discussionmentioning
confidence: 99%
“…In reports on uALB, uRBP, or uNAG in canine or feline urine, cystocentesis as well as catheterization and midstream voided urine have been used. 12,19,30 In contrast to voided samples, cystocentesis avoids contamination with lower urinary tract epithelial cells, proteases, and bacteria that may affect urinary markers. 22 When performing cystocentesis, care must be taken to avoid peripheral blood contamination leading to grossly discolored urine samples, since this may cause a falsely increased urinary albumin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…A calibration of the human nephelometric assay (BNII system, Kit N AS ALB, Siemens Healthcare) was deemed necessary because the monoclonal antibody against human albumin used in the assay shared only a partial cross-reactivity with canine albumin (Gentilini et al, 2005;Murgier et al, 2009). A calibration curve was constructed by diluting a solution of purified canine albumin (Canine Albumin Protein ab119814, Abcam) to concentrations varying between 1.6 and 100 mg/dL using 0.9% saline.…”
Section: Analysesmentioning
confidence: 99%